Find the value of c that makes each trinomial a perfect square. Then write the trinomial as a perfect square.

x^{2} - 2.2x + c

perfect square trinomials can be factored into identical binomials,

(x + a)^{2} = (x + a)(x + a) = x^{2} + 2ax + a^{2}

Compare the general form to your expression

x^{2} **+ 2a**x + a^{2}

x^{2} **- 2.2**x + c

We need to find the value of **a** and square it to replace **
c = a ^{2}**

if **2a = -2.2**

a = -1.1, then **a ^{2} = (-1.1)^{2} = 1.21**

**x ^{2} - 2.2x + 1.21** = perfect square trinomial, which factors into (x + a)

^{2}, and we found

**a = -1.1**

**(x - 1.1) ^{2} **